The influence of roa, roe, and der on stock price with dividend policy as an intervening variable - Mohammad Wasil; Pinky Pininta Dewi; Andini Putri Arafah (Indonesia Accounting Research Journal, 2022)
This study aims to determine the effect of ROA, ROE, and DER on stock prices with dividend policy as an intervening variable. This research is a quantitative research. The sample used in this study were 8 companies that were taken using the purposive sampling method that met certain criteria from a population of 30 food and beverage companies on the IDX for the 2017-2020 period. The data processing of this research was carried out using the multiple linear regression method with SPSS version 25. The results of this study indicate that ROA, ROE and DER have no significant positive effect on stock prices. Meanwhile, the dividend policy assessed by the DPR has a significant positive effect on stock prices. The results of path analysis in this research state that the effect of ROA, ROE and DER on stock prices is greater through dividend policy as an intervening variable (indirect effect) than its direct effect on stock prices.